Chemoenzymatic synthesis of unmodified heparin oligosaccharides: cleavage of p-nitrophenyl glucuronide by alkaline and Smith degradation. Issue 5 (16th January 2017) - Zhang, Xing; Xu, Yongmei; Hsieh, Po-Hung; Liu, Jian; Lin, Lei; Schmidt, Eric P.; Linhardt, Robert J.
Abstract : A heparin oligosaccharide having a completely natural structure was successfully synthesized through a chemoenzymatic approach using an unnatural glycosyl acceptor, p -nitrophenyl glucuronide (GlcA- p NP). Abstract : A heparin oligosaccharide having a completely natural structure was successfully synthesized through a chemoenzymatic approach using an unnatural glycosyl acceptor, p -nitrophenyl glucuronide (GlcA- p NP). The use of an inexpensive and commercially available GlcA- p NP acceptor facilitates oligosaccharide recovery and purification on C-18 resin during chemoenzymatic synthesis. Oligosaccharide chain extension and modification afforded a heptasaccharide with gluconic acid residues at its reducing and non-reducing ends. Treatment with periodate oxidation followed by Smith degradation or alkaline elimination resulted in the selective cleavage of vicinal diol-containing glucuronic acid residues affording highly sulfated heparin pentasaccharides having a completely natural structure. This methodology should facilitate the chemoenzymatic synthesis of a family of highly sulfated heparin oligosaccharides with unmodified structures for biological evaluation.